Evaluation of lipidomic change in goat sperm after cryopreservation - Xu, Bingbing; Wang, Ruijun; Wang, Zhiying; Liu, Hongfu; Wang, Zhen; Zhang, Weihang; Zhang, Yanjun; Su, Rui; Liu, Zhihong; Liu, Yongbin; Li, Jinquan; Zhang, Jiaxin (Frontiers in Veterinary Science, 2022)
The current study aimed to detect the relationship between the spermatozoa cryotolerance and the post-thawed sperm lipidome. Ejaculates from 20 goats, and performed a uniform frozen-thawed procedure in this study. According to the total motility of thawed sperm of goats, semen samples were classified into HF group (High Freezers, n = 8) with >60% total motility and LF group (Low Freezers, n = 8) with < 45% total motility. The lipidomic analysis based on UHPLC-MS/MS was utilized to investigate the relationship between sperm cryotolerance and their lipid metabolites expression. The results showed that the cryotolerance of sperm from different individual goats were in great variation. The total motility of post-thawed sperm in HF group (60.93 ± 2.43%) is significantly higher than that in LF group (34.04 ± 3.41%, P < 0.01). And the post-thawed sperm in HF group exhibited significantly higher plasma membrane (59.06 ± 2.34%) and acrosome integrity (62.93 ± 1.15%) than that in LF group (34.06 ± 4.85%, 44.92 ± 2.19% respectively, P < 0.01). The total of 29 lipid subclasses and 1,133 lipid molecules in the post-thawed goat sperm were identified by lipidomics analysis. The lipid content of thawed sperm in HF group was higher than that in LF group, the lipid profile in HF group was significantly separated from LF group, which indicated that the difference in lipid composition and lipid metabolism mode of sperm between the two groups was existed, especially the expression of phosphatidylcholine and triglyceride molecules. In conclusion, the cryotolerance of sperm from different individual goats were in great variation. Sperm with high cryotolerance may be able to uptake more lipids during cryopreservation. The increase in phosphatidylcholine and triglyceride content of thawed. Sperm may relate to more active lipid anabolic processes.